The Role of Frontal Assessment Battery and Frontal Lobe Single-Photon Emission Computed Tomography in the Differential Diagnosis of Progressive Supranuclear Palsy Variants and Corticobasal Syndrome—A Pilot Study - Alster, Piotr; Migda, Bartosz; Madetko, Natalia; Duszyńska-Wąs, Karolina; Drzewińska, Agnieszka; Charzyńska, Ingeborga; Starczyński, Miłosz; Szepelska, Ada; Królicki, Leszek; Friedman, Andrzej (Frontiers in Neurology, 2021)
Progressive Supranuclear Palsy (PSP) and Corticobasal Syndrome (CBS) are clinical syndromes classified as atypical parkinsonisms. Due to their overlapping symptomatology, recent research shows the necessity of finding new methods of examination of theses clinical entities. PSP is a heterogenic disease. PSP Richardson-Steele Syndrome (PSP-RS) and Parkinsonism Predominant (PSP-P) are the most common clinical variants of Progressive Supranuclear Palsy Syndrome (PSPS). The different clinical course and life expectancy of PSP-RS and PSP-P, stress the need of efficient examination in the early stages. The aim of the study was to evaluate the possible feasibility of the combined use of Frontal Assessment Battery (FAB) and Single Photon Emission Computed Tomography (SPECT) in the differentiation of PSP-RS, PSP-P and CBS. The findings show that FAB may be interpreted as a possible supplementary tool in the differential diagnosis of PSP-P and PSP-RS. The differences in SPECT are less pronounced. The study does not show any advantages of performing combined frontal SPECT and FAB assessment in the differential examination of PSP and CBS. Moreover PSP-RS and CBS in a detailed evaluation of the frontal lobe, do not show any significant differences. This is a relatively small study, however highlighting relevant features of clinical examination of these rare entities.